2011
DOI: 10.2337/db10-0627
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Methylglyoxal Infusion by Minipump Causes Pancreatic β-Cell Dysfunction and Induces Type 2 Diabetes in Sprague-Dawley Rats

Abstract: OBJECTIVEThe incidence of high dietary carbohydrate-induced type 2 diabetes is increasing worldwide. Methylglyoxal (MG) is a reactive glucose metabolite and a major precursor of advanced glycation end products (AGEs). MG levels are elevated in diabetic patients. We investigated the effects of chronic administration of MG on glucose tolerance and β-cell insulin secreting mechanism in 12-week-old male Sprague-Dawley rats.RESEARCH DESIGN AND METHODSMG (60 mg/kg/day) or 0.9% saline was administered by continuous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 40 publications
9
140
0
3
Order By: Relevance
“…Previous reports have shown that MGO alters insulin secretion [17,19,21]. Our current study on INS-1E cells further documents the inhibitory effect of MGO on glucoseinduced insulin secretion, but clearly goes beyond by providing decisive insight into the mechanisms involved.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous reports have shown that MGO alters insulin secretion [17,19,21]. Our current study on INS-1E cells further documents the inhibitory effect of MGO on glucoseinduced insulin secretion, but clearly goes beyond by providing decisive insight into the mechanisms involved.…”
Section: Discussionsupporting
confidence: 50%
“…We have also shown that MGO induces insulin resistance in skeletal muscle cells through direct chemical modification of IRS proteins [15]. Finally, MGO is thought to exert deleterious effects on insulin secretion [16][17][18][19][20][21]. However, the molecular mechanisms involved in the effect of MGO on the regulation of insulin release remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…We have already noted that excess methylglyoxal exposure can lead to diabetes. Direct evidence of this was obtained when methylglyoxal injection into Sprague Dawley rats caused pancreatic β-cell dysfunction [164]. We earlier discussed the rôle of excess iron deposition in the destruction of pancreatic β cells [134].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…More direct evidence of interaction of alagebrium and MG using mass spectrometry would be very useful. We have also recently shown that alagebrium significantly attenuated the deleterious effects of chronic MG administration for 4 wks on glucose tolerance and pancreatic islet -cell function in male Sprague-Dawley rats [72].…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Sprague-Dawley rats [72]. Elevated MG levels are linked to the development of microvascular complications of diabetes such as retinopathy and nephropathy, and other conditions such as atherosclerosis and neurodegenerative diseases [73][74][75][76][77].…”
Section: Pharmacology 686mentioning
confidence: 99%